EFFECT OF EXPERIMENTALLY INFECTION LAYERS WITH LISTERIA MONOCYTOGENES ON SOME BLOOD FEATURES - Al-Rubaiey, Methaq G.; Al-Obaidi, Faris A. (The Iraqi Journal of Veterinary Medicine, 2010)
The object of this study was to determine the effect of experimentally infection dose of layers orally on some blood components. A total of 45 layer were distributed into three groups and each group to three replicates (15 layer per replicate) cosnsisted of T1 (controlgroup free of infection ) , T2 and T3 were orally experimentally infected by 1x105and 1x1010(CFU \ ml \ hen of L.monocytogenes . The results of blood tests showed that T1 layer predominant in P.C.V. , Hb , and R.B.Cs. after 6 days of experimentally infection and this differences disappeared after 35 days , when as the differences in W.B.C.s appeared after 9 days and total protein concentration after 21 days and disappeared after 42 days of experimentally infection with no statistically differences in uric acid concentration .